2020
DOI: 10.1136/bcr-2019-232115
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to dementia diagnosis and care in China

Abstract: In China, the ageing population and the prevalence of dementia are projected to escalate significantly by 2050 resulting in a substantial increase in health and economic burden on caregivers, healthcare facilities, healthcare providers and communities. There is no published national dementia policy or strategy in China. This case report describes significant barriers contributing to diagnostic problems and inadequate care of dementia through the case of an older female in rural China, whose condition deteriora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Gaps still existed in dementia diagnosis in rural and urban areas with 93.5% of patients being undetected in rural areas and 77.5% being undetected in urban. This might be due to rural elderly residents having lower awareness and worse medical conditions when compared to urban residents or due to the higher prevalence of dementia in rural areas than in urban areas (13). This study also found that in urban areas, the proportion of undetected dementia increased with age before 75 years but decreased with age after 75 years.…”
Section: Discussionmentioning
confidence: 49%
“…Gaps still existed in dementia diagnosis in rural and urban areas with 93.5% of patients being undetected in rural areas and 77.5% being undetected in urban. This might be due to rural elderly residents having lower awareness and worse medical conditions when compared to urban residents or due to the higher prevalence of dementia in rural areas than in urban areas (13). This study also found that in urban areas, the proportion of undetected dementia increased with age before 75 years but decreased with age after 75 years.…”
Section: Discussionmentioning
confidence: 49%
“…Several of them become overly protective and resort to using punitive approaches, such as blaming, isolation and physical restraint, to control the residents. Attitudes and behaviours of the care home staff seem largely because they lack knowledge and skills in managing challenging behaviours (Cooke et al, 2014 Quail et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Literature generally showed that dementia care has not been provided widely in the country because both formal and informal carers, including healthcare professionals, care workers and family members, in community and care facilities lack relevant caregiving knowledge and skill (Wang, Cheung, et al, 2019). Particularly, Quail et al (2020) identified that limited accessibility to specialist services for dementia diagnosis and care, limited availability of dementia-related training for healthcare providers, and poor awareness of care needs of people with dementia as the major challenges in dementia care in China. Wu et al (2016) and Zhang et al (2020) found that some residential care facilities refused to admit people with dementia due to a lack of trained care staff in dementia care.…”
Section: Introductionmentioning
confidence: 99%
“…Among the global population in 2017, nearly a quarter of the population over 60 was living in China; the population over 60 in China is estimated to increase to 478.9 million people by 2050 [5]. The significant increase in the ageing population will lead to a substantial increase in demand for health workers [6].…”
Section: Introductionmentioning
confidence: 99%